2020
DOI: 10.5115/acb.20.039
|View full text |Cite
|
Sign up to set email alerts
|

The distribution pattern of the dorsal cutaneous nerves of the foot and its clinical implications

Abstract: Iatrogenic injury to subcutaneous nerves on the dorsum of the foot is an established risk factor during the surgical procedures resulting in postoperative pain, sensation loss and painful neuroma. Previous studies have reported on the distribution pattern of the superficial peroneal, deep peroneal and sural nerves (SNs) and their branches with various classifications about specific populations. The purpose of the present study was to evaluate the distribution pattern and classification of the nerves on the dor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…LDCN injury is a rare injury that may result from a lateral ankle sprain or damage during surgeries or procedures performed for the Achilles tendon and lateral side of the ankle [7,8] . The LDCN branches out as the SN passes under the lateral malleolus, and it is responsible for the sensory innervation of the dorsolateral aspect of the foot [5–7] . SN conduction is important for diagnosing nerve damage or entrapment and is the most useful test for detecting electrophysiological abnormalities in neuropathy cases [7] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LDCN injury is a rare injury that may result from a lateral ankle sprain or damage during surgeries or procedures performed for the Achilles tendon and lateral side of the ankle [7,8] . The LDCN branches out as the SN passes under the lateral malleolus, and it is responsible for the sensory innervation of the dorsolateral aspect of the foot [5–7] . SN conduction is important for diagnosing nerve damage or entrapment and is the most useful test for detecting electrophysiological abnormalities in neuropathy cases [7] .…”
Section: Discussionmentioning
confidence: 99%
“…It is responsible for the cutaneous sensations in the posterior and lateral aspects of the legs, lateral calcaneal area of the distal third of the legs, and lateral aspect of the feet and fifth toes. [ 5 , 6 ] The SN originates from medial and lateral cutaneous nerves branching from each of the tibial and common peroneal nerves, joining just distal of the popliteal fossa. It then descends between the two heads of the gastrocnemius muscle and passes through the lateral margin of the calcaneal tendon and between the lateral malleolus and calcaneus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,10,26 The branching pattern and location of the distal is variable and may also give off an anastomotic branch (AB) to the intermediate dorsal cutaneous nerve, which travels distally along the dorsal aspect of the foot to provide sensory innervation to the third, fourth, and fifth digits. 16,24 Previous cadaveric studies have observed a frequency of AB ranging from 24% to 63%. 1,9,10,17,30…”
Section: Introductionmentioning
confidence: 99%
“…It can be of great help to anesthetics while giving local anesthetic block (8)(9)(10)(11)(12)(13)(14). There are studies done by authors Cheredath et al [15], Inchai, Vaseenon, et al [16], V Nayak, et al [17] which describe the innervation pattern on dorsum of the foot according to the areas supplied by sural nerve, superficial perineal nerve and deep perineal nerve. Carla Gabrielli et al [18] have studied the topographic anatomy of superficial perineal nerve on dorsum of the foot.…”
mentioning
confidence: 99%